Precision and Purpose Airpower in the Libyan Civil War - Mueller, Karl P. (Research Reports, 2015)
A team of U.S. and international experts assesses the impact of various nations' airpower efforts during the 2011 conflict in Libya, including NATO allies and non-NATO partners, and how their experiences offer guidance for future conflicts. In addition to the roles played by the United States, Britain and France, it examines the efforts of Italy, Canada, Belgium, Denmark, the Netherlands, Norway, Sweden, Qatar, the UAE, and the Libyan rebels.